AB0413 Systemic Therapy in Primary Sjögren Syndrome Patients. (15th July 2016) - Fernandez Castro, M.; Andreu, J.L.; Sanchez-Piedra, C.; Martinez Taboada, V.; Olive, A.; Rosas, J.; ,
Abstract : Background: Primary Sjögren syndrome (pSS) is a systemic autoimmune disease involving mainly the exocrine glandular system. Nevertheless, its clinical spectrum includes the development of multiple extra-glandular manifestations which will be determinant for the use of systemic therapy. Objectives: The aim of our study was to describe the systemic therapy in a pSS cohort assisted in Spanish Rheumatology Departments and its association with the involvement of different organs. Methods: This is a multicenter descriptive transversal study of pSS patients fulfilling European/American consensus criteria. Patients were included by randomization from thirty-three Rheumatology departments. Data were collected by reviewing clinical records and interviewing the patients. Informed consent was obtained and local ethics committees approved the study. Variables were analysed by descriptive statistical methods, using means, medians, and rates. Chi-square was used to establish the statistical associations, being considered a p<0, 05 as significant. Results: Four hundred and thirty-seven patients were included. Ninety-five percent of them were women. The median age of the cohort was 58 years. Eighty-four percent of the patients have been treated (currently or previously) with non-steroidal anti-inflammatory drugs (NSAID), 49% had been treated with glucocorticoids (GC), 7% with boluses of GC, 51% with antimalarial, 13% with methotrexate (MTX), 10% with azathioprine (AZA), 4% with mycophenolate mofetil (MM) and 3% with cyclophosphamide (CF). NSAIDs were significantly used more frequently in patients with joint involvement. GC were significantly used more frequently in patients with joint, pulmonary, central and peripheral nervous system (CNS and PNS) involvement and cytopenia. GC boluses were used significantly more frequently in patients with musculoskeletal, pulmonary and nervous system involvement. Antimalarials were significantly used more frequently in patients with joint involvement. MTX was significantly used more frequently in patients with joint, CNS involvement and cytopenia. AZA was significantly used more frequently in patients with lung and CNS involvement and cytopenia. MM was significantly used more frequently in patients with renal, lung and PNS involvement, and cytopenia. CF was significantly used more frequently in patients with joint, pulmonary, CNS and PNS involvement. Conclusions: Despite the absence of clinical controlled studies demonstrating efficacy and safety, systemic therapy use in SSp patients is very frequent. Its use is mainly associated with the presence of musculoskeletal, neurological, pulmonary and haematological manifestations. Disclosure of Interest: None declared